Enhancing Graduate Students’ Ability to Conduct and Communicate Research through an Interdisciplinary Lens - Gili Marbach-Ad (American Society for Microbiology, 2018)
This research is a part of a longitudinal study of the Computation and Mathematics for Biological Networks (COMBINE) program at the University of Maryland. The mission of COMBINE is to train doctoral students from a wide range of fields to pursue interdisciplinary research. Here, we focus on one component of COMBINE, a semester-long course titled Data Practicum at the Intersection of the Physical, Computer, and Life Sciences. The goal of this study was to explore the effectiveness of the teaching practices that were used in the Data Practicum. We investigated their impact on graduate students’ confidence to conduct research through an interdisciplinary lens and to communicate their research to diverse audiences. We used validated pre- and post-course online surveys, in-class observations, collection of artifacts, and interviews. Interviewed students and instructors highlighted the course’s iterative process, peer review system, and unique incorporation of outside research already being conducted by students as the most impactful aspects of the course. Based on students’ reports and artifacts, the Data Practicum was successful in helping them to communicate their research visually, orally, and in text to a wide and varied audience, to critically review others’ work, inside and outside their discipline, and to develop awareness of research in other disciplines. We observed that it is possible to enhance interdisciplinary communication skills through an iterative teaching approach that gives students a chance to incorporate feedback from multiple sources. This course could serve as a model for other graduate programs wishing to increase training in interdisciplinary skills.